ANALYZING FACTORS INFLUENCING THREADS PLATFORM ADOPTION AMONG INDONESIAN GENERATION Z: A MODIFIED UTAUT APPROACH WITH USER SATISFACTION AND INERTIA - Rompas, Reinaldo Ragil; Fajar, Ahmad Nurul (LPPM Universitas Jambi, 2026)
The Threads platform reached 100 million signups in five days but experienced a drastic decline in users, indicating challenges in maintaining sustainable adoption. This study aims to analyze the factors influencing Threads adoption among Indonesian Generation Z using a modified UTAUT framework with the addition of User Satisfaction and Inertia constructs. This study used a quantitative approach with 474 valid respondents from Generation Z in six Indonesian provinces through purposive sampling. Data were analyzed using PLS-SEM through SmartPLS 4.0 to test nine research hypotheses. The measurement model confirmed adequate validity and reliability. The structural model showed substantial explanatory power with R² of 0.717 (Intention to Use), 0.681 (Actual Use), and 0.585 (User Satisfaction). Eight of the nine hypotheses were supported. User Satisfaction is the strongest predictor of Intention to Use (β=0.652), Intention to Use predominantly influences Actual Use (β=0.801), Performance Expectancy predicts User Satisfaction (β=0.579), and Social Influence influences Intention to Use (β=0.279). Inertia has a significant negative effect on Intention to Use (β=-0.122), confirming that habitual attachment to X (formerly Twitter) hinders Threads adoption. Facilitating Conditions are insignificant on Intention to Use but have a direct effect on Actual Use. The novelty of this study lies in the integration of User Satisfaction and Inertia constructs into UTAUT for the context of competitive social media platform switching, which has not been widely explored in the literature. Practically, Meta needs to prioritize improving user experience and addressing switching barriers to sustain Threads adoption in the Indonesian market.